PENGARUH PAJAK, TUNNELING INCENTIVE, DAN MEKANISME BONUS TERHADAP KEPUTUSAN PERUSAHAAN MELAKUKAN TRANSFER PRICING - Nur Fitria Fauziah; Akhmad Saebani (Universitas Kristen Krida Wacana, 2018)
This study aims to determine the effect of Taxes, Tunneling Incentive, and Bonus Mechanism on The Company’s Decision to Transfer Pricing. The study uses all of the manufactur companies and mining companies in the coal sector listed on Indonesian Stock Exchange (BEI) in 2014, 2015 and 2016. Sampling technique using purposive sampling (purposive sampling method). Selection of a sample of 90 manufacturing companies and mining companies in the coal sector listed in Indonesia Stock Exchange. Testing the hypothesis is used multiple linear regression analysis with SPSS 23 and a significance level of 5% (0,05). The results of the testing showed that : (1) there is influence of Tax measured by effective tax rate (ETR) with a significance level of 0,020 is smaller than the specified level = 0,05, (2) there is influence of Tunneling Incentive which is measured based on the amount of foreign ownership exceeding 20% to Transfer Pricing with a significance level of 0,002 is smaller than the specified level = 0,05, there is no significance influence of Bonus Mechanism as measured by net profit trend index (ITRENDLB) to Transfer Pricing with a significance level of 0,340 is greater than the specified level = 0,05.Keywords : bonus mechanism, tax, transfer pricing, tunneling incentive